Synoyms and homonyms as seen in comparative linguistics - Key, Mary Ritchie (Lenguas Modernas, 2017)
The notion of "synonym" can be explored by examining the building blocks that are used to create words in American Indian languages. Universal cognitive processes are similar between speakers of Indo-European languages and non-Western languages, as seen in such concepts as ’up’ and ’down’. Culturally learned cognitive relationships, as exemplified in language, give us some insight into meaning, and how the mind works.